Pemilihan di Masa Krisis: Refleksi Dampak Media Pemberitaan Terhadap Kepercayaan Dan Partisipasi Politik di Tengah Krisis Kesehatan Covid-19 - Hasbullah Azis (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of news media is believed by most researchers to be proven to be able to influence people's political beliefs which then facilitate people's participation in the political process. Political trust in the government and other political institutions is a key indicator of public participation in the democratic process. Specifically, this research aims to test the extent to which media exposure to information regarding the Covid-19 virus outbreak influences people's political trust in one of the regions that has the highest rate of Covid-19 cases in Indonesia and is holding regional head elections during a pandemic. Apart from that, this research also tests whether there is a relationship between political trust and the level of electoral participation during a pandemic. By surveying 211 respondents, this research found several findings. First, even during a health crisis due to the Covid-19 virus outbreak and concerns about being exposed to the virus, the level of public participation in the 2020 Local Election tends to be high. Second, the use of information media affects people's political trust during the pandemic. Third, political trust resulting from exposure to media reports has a positive correlation with the level of public participation in the Regional Head Election during the Covid-19 pandemic